Alternative educational spaces and “school failure”: on the possibilities in a porous placement zone (Praxis Educativa, 2012)
This Ph.D research project studies the relationship between alternative educational spaces (AES) –in conventional and formal education, and the learning of children who have been portrayed as “failure students” by the educational system. It is intended to think in what way changes in the configuration of institutional spaces aimed at learning, have had an influence on primary education and if it is possible to help these children recover or develop a strong wish for learning in educational institutions. It is posible to say that the case studied functions as an AES. What I here state is that its placement in a porous zone operates as a condition of alternative functioning and, simultaneously, constitutes one of its results. Being the case situated in three organizational contexts allows escaping from external regulations and its placement in a net that seems to contribute to the installation of psico social filiation and transmission processes.
Keywords: alternative educational spaces; porous zone; condition; institutional result; nets